Replacing PLC controller with PIC - Bader, Sami; Abu Amriah, Mahmmoud (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2011)
This project aims to replace a PLC microcontroller with a PIC microcontroller in order to find an engineering alternative solution for saving money , in order to achieve the purpose, the main target is to design an industrial application that is operated by PIC microcontroller and some necessary connection circuits , and to simulating the PLC with C program. The application we chose is a packaging machine of sugar bags of one kilogram, which contain 3 phase motor with 120 watt to drive the conveyor (2meter) which moves the filled bag to package.
case: packaging machine of sugar bags
Keywords: PLC controller